Microring Resonators and Silicon Photonics. Issue 48 (23rd May 2016) - Ramiro-Manzano, Fernando; Biasi, Stefano; Bernard, Martino; Mancinelli, Mattia; Chalyan, Tatevik; Turri, Fabio; Ghulinyan, Mher; Borghi, Massimo; Samusenko, Alina; Gandolfi, Davide; Guider, Romain; Trenti, Alessandro; et al.
ABSTRACT: Silicon Photonics is the technological to face the future challenges in data communications and processing. This technology follows the same paradigm as the technological revolution of the integrated circuit industry, that is, the miniaturization and the standardization. One of the most important building blocks in Silicon Photonics is the microresonator, a circular optical cavity, which enables many different passive and active optical functions. Here, we will describe the new physics of the intermodal coupling, which occurs when multi radial mode resonators are coupled to waveguides, and of the optical chaos, which develops in coupled sequence of resonators. In addition, an application of resonators in the label-free biosensing will be discussed.